KNOWLEDGE, ATTITUDES AND BEHAVIOR OF DOG OWNERS TOWARDS RABIES IN BANJAR SELAT TENGAH, SELAT VILLAGE, BANGLI REGENCY - I Made Abhiwedam Pasek; I Wayan Masa Tenaya; I MAde Sukada (Buletin Veteriner Udayana, 2024)
Rabies is a zoonotic disease caused by a neurotropic virus of the genus Lyssavirus in the Rhabdoviridae family. Rabies cases were detected in Bali in November 2008 in Badung Regency and spread gradually in all regencies, one of which was Bangli Regency. The purpose of this study was to determine the level of knowledge, attitudes and behavior of the people in Banjar Selat Tengah. The design of this research is observational. The method used was a survey of respondents, namely all dog-owning households in Banjar Selat Tengah, Selat Village. Based on data obtained from 34 (100%) respondents, namely from Banjar Selat Tengah, that the majority of the population has a good level of knowledge, attitude and behavior. Based on the results of the research that has been done, it shows that the level of knowledge of the people of Banjar Selat Tengah about rabies is good at 94.1%. In addition, the attitude of the Banjar Selat Tengah community can be categorized as a positive attitude of 79.4%. For the level of behavior of the Banjar Selat Tengah community, it is classified as good behavior at 79.4%. Based on the results of the study, it can be concluded that the number of families who keep dogs from Banjar Selat Tengah is 34 families. The majority of the banjar residents have a good level of knowledge, so does the community's attitude towards rabies which is also in the category of positive attitudes and the community's behavior towards rabies is quite good. It is hoped that the community can improve their knowledge, attitude and behavior towards rabies to help better manage rabies in the future.